1979
DOI: 10.1515/jpme.1979.7.4.202
|View full text |Cite
|
Sign up to set email alerts
|

Acid base balance in pre-eclamptic, hypertensive and diabetic pregnancies. Maternal blood and amniotic fluid studies

Abstract: 202Fadel et al., Acid base balance in maternal blood and amniotic fluid J. Perinat. Med.Acid base balance in pre-eclamptic, hypertensive and diabetic pregnancies. Maternal 7 (1979) 195 Wood ^ ^ ^ fl ui d studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…42 Fadel et al reported no significant difference between arterial levels of lactic acid in women with preeclampsia and healthy pregnant controls. 43 An attempt to use venous lactic acid levels early in pregnancy as a predictor for onset of preeclampsia was not successful. 15 Specific levels of lactic acid reported should be interpreted with caution because many of the studies reporting lactic acid levels did not clarify whether or not patients were in labor at the time of collection.…”
Section: Discussionmentioning
confidence: 99%
“…42 Fadel et al reported no significant difference between arterial levels of lactic acid in women with preeclampsia and healthy pregnant controls. 43 An attempt to use venous lactic acid levels early in pregnancy as a predictor for onset of preeclampsia was not successful. 15 Specific levels of lactic acid reported should be interpreted with caution because many of the studies reporting lactic acid levels did not clarify whether or not patients were in labor at the time of collection.…”
Section: Discussionmentioning
confidence: 99%